FAKTOR YANG MEMPENGARUHI FIRM VALUE DENGAN MEDIASI PROFITABILITY PADA PERUSAHAAN SEKTOR PROPERTI - Erryka Goritman; Henryanto Wijaya (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
The goal of this study is to empirically examine the effect of firm’s capital structure, managerial ownership, and firm size on the firm value through profitability mediation in property sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The samples in this study are 153 companies selected using purposive sampling method. Data processing techniques using SEM-PLS method helped by SmartPLS 4.0.8.4. The results showed that firm value and profitability were positively but not significantly influenced by capital structure, while managerial ownership and firm size had a negative but not significant effect on firm value and profitability. Firm value is negatively and not significantly affected by profitability, and profitability does not succeed in mediating the effect of capital structure, managerial ownership, and firm size on firm value. The implication of this study is the need to consider external factors in determining firm value.